2019
DOI: 10.3892/wasj.2019.11
|View full text |Cite
|
Sign up to set email alerts
|

Effects of irradiated cell conditioned medium on the response of human lung cancer cells to anticancer treatment in vitro

Abstract: Ionizing radiation induces a cellular response not only in the irradiated cells, but also in the neighboring non-irradiated cells, and this effect is known as the radiation-induced bystander effect. The irradiated cells transmit signals to the non-irradiated cells via gap junctions or soluble factors, exerting biological effects on the neighboring non-irradiated cells. In this study, we investigated the effects of irradiated cell conditioned medium (ICCM) on the response of human lung cancer cells (A549 and H1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…In addition, wound healing assay further confirms the migration ability of HUVECs in that, the percentage of wound healing rate dose-dependently increased at the endpoint of exposure. More recently, it was demonstrated that the CMs collected from irradiated human lung cancer cells enhanced the non-irradiated cells’ migration rate [40]. These results highlight the induction of migration responses of HUVECs against irradiated CMs, however the underlying mechanisms largely remain unknown.…”
Section: Discussionmentioning
confidence: 90%
“…In addition, wound healing assay further confirms the migration ability of HUVECs in that, the percentage of wound healing rate dose-dependently increased at the endpoint of exposure. More recently, it was demonstrated that the CMs collected from irradiated human lung cancer cells enhanced the non-irradiated cells’ migration rate [40]. These results highlight the induction of migration responses of HUVECs against irradiated CMs, however the underlying mechanisms largely remain unknown.…”
Section: Discussionmentioning
confidence: 90%
“…Other studies explored radioresistance induction and showed that CM from previously irradiated cells also showed protective effects in the A549 cells upon additional X-ray exposure, leading to lower apoptotic rates [4]. CM from three types of previously irradiated lung cancer cells facilitated decreased cell death upon irradiation of sensitive cells via increased plasminogen activator inhibitor-1 (PAI-1) that upregulated AKT and ERK1/2 pathways and inhibited caspase-3 activity [5].…”
Section: Conditioned Mediamentioning
confidence: 99%